2022
DOI: 10.3390/ijerph191710572
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Analysis of the Tubular and Glomerular Effects of Chronic Exposure to Environmental Cadmium

Abstract: We retrospectively analyzed data on the excretion of cadmium (ECd), β2-microglobulin (Eβ2M) and N-acetyl-β-D-glucosaminidase (ENAG), which were recorded for 734 participants in a study conducted in low- and high-exposure areas of Thailand. Increased Eβ2M and ENAG were used to assess tubular integrity, while a reduction in the estimated glomerular filtration rate (eGFR) was a criterion for glomerular dysfunction. ECd, Eβ2M and ENAG were normalized to creatinine clearance (Ccr) as ECd/Ccr, Eβ2M/Ccr and ENAG/Ccr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In contrast, the BMDL values of E Cd /E cr associated with a 5% eGFR decline could not be reliably determined (U/L ratios of 10 4 –10 5 ). These findings were consistent with data from a conventional dose–response analysis, where an inverse relationship between E Cd and eGFR became statistically significant only when E Cd was normalized to C cr [ 42 ].…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, the BMDL values of E Cd /E cr associated with a 5% eGFR decline could not be reliably determined (U/L ratios of 10 4 –10 5 ). These findings were consistent with data from a conventional dose–response analysis, where an inverse relationship between E Cd and eGFR became statistically significant only when E Cd was normalized to C cr [ 42 ].…”
Section: Discussionsupporting
confidence: 88%
“…The impact of Cd exposure on GFR has long been underestimated due to the common practice of normalizing E Cd to E cr . The comparability of guidelines between populations could be improved by the universal acceptance of a consistent normalization of E Cd to Ccr that eliminates the effect of muscle mass on E cr , thereby giving a more accurate assessment of the severity of Cd nephropathy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This tolerable intake level for Cd was derived from a risk assessment model that assumed an increase in excretion of β 2 -microglobulin (β 2 M) (E β2M ) above 300 μg/g creatinine as the point of departure (POD) [ 8 ]. However, we have shown that such an increase in E β2M reflected tubular dysfunction and nephron loss, evident from a reduction in estimated glomerular filtration rate (eGFR) to 60 mL/min/1.73 m 2 or below [ 9 , 10 ]. In effect, a tolerable intake level of Cd derived from the E β2M -based POD is not sufficiently low to be without an impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…For C cr -normalized data, kidney tubular dysfunction was defined as (E β2M / C cr ) × 100 ≥ 300 µg/L of filtrate [25]. Microalbuminuria and macroalbuminuria were defined as (E Alb /C cr ) × 100 ≥ 20 and 200 mg/L of filtrate, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Macroalbuminuria was not found in controls, but was present in 11.4-13.3% of those with DM. The overall % of mild and severe tubular dysfunction, defined as (E β2M /C cr ) × 100 ≥ 300 and ≥1000 µg/L filtrate [25] were 66.2%, and 32.4%, respectively. More than half (57.7%) of the ≥10-DM group has severe tubular proteinuria.…”
Section: Characteristics Of the Study Subjectsmentioning
confidence: 98%